(untitled) (Research, Society and Development, 2023)
The study aimed to demonstrate the perspectives of Accounting students at Unitins on entrepreneurial skills. To this end, we sought to identify the existence of 10 entrepreneurial skills in a sample of 40 students. For this, a questionnaire with an internal consistency of Cronbach’s alpha above 0.8 was used, as a data collection instrument structured in 10 blocks of questions that collect the level of agreement in a 5-point lirket scale, each block being corresponding to a type of competency. The results show that all skills were present in the students, but some were more present than others. Such variations can cause positive effects, but most of these occurrences emerge under negative effects to the emergence and maintenance of new enterprises. This interpretation was only possible after a detailed investigation based on the review of studies, since the investigation of the quantitative analysis of the results did not efficiently demonstrate the degree of manifestation of competences.